Substitution of raw lucerne with raw citrus lemon by-product in silage: In vitro apparent digestibility and gas production - Besharati, Maghsoud; Palangi, Valiollah; Salem, Abdelfattah Zeidan Mohamed; De Palo, Pasquale; Lorenzo, Jose Manuel; Maggiolino, Aristide (Frontiers in Veterinary Science, 2022)
Fruit pomace addition to lucerne silage could rapidly reduce silage pH creating an acidic environment, and thus maybe preventing spoilage. However, the purpose of this study was to investigate the effect of different rates of inclusion of citrus lemon by-products to lucerne. In this study, 5 different treatments were prepared: L0 (control) with 100% lucerne; L25 (75% lucerne with 25% lemon pomace); L50 (50% lucerne with 50% lemon pomace); L75 (25% lucerne with 75% lemon pomace); and L100 (100% lemon pomace). After ensiling, the chemical composition, nutritive value, stability, in vitro apparent digestibility, and gas production of silage were determined. The DM content resulted higher for lemon pomace substitution equal or exceeded 50% (P < 0.01). Crude protein, on the contrary, decreased (P < 0.01) over the same percentage of substitution. The L100 and L75 treatments showed higher dry matter apparent disappearance rate and lower (P < 0.05) crude protein and neutral detergent fiber apparent degradation rate versus L0. Lemon pomace could be used at high inclusion level in lucerne silage, allowing the preservation of this by-product all the year, improving some chemical silage characteristics, and reducing proteolytic processes that usually happen on lucerne silage. Moreover, the in vitro apparent digestibility and gas production results showed that a partial substitution of lucerne with lemon pomace is able to improve silage digestibility.